2020
DOI: 10.1096/fj.201902280r
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 contributes to pregnancy‐induced hypertension development by enhancing oxidative stress and inflammation through the regulation of the miR‐150‐5p/ET‐1 axis

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been identified previously in the pathogenesis of hypertension and some gestational diseases. However, the biological functions of MALAT1 in pregnancy-induced hypertension (PIH) are still poorly understood. Herein, we aim to explore the functional relevance of MALAT1 in PIH and to explain the potential underlying mechanisms. We found that the levels of ET-1 and MALAT1 were upregulated and that of miR-150-5p were downregulated in the serum of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…It has been proven that ROS play an important role in the pathophysiological process of hypertension. Increased oxidative stress is an important mediator of endothelial damage in hypertension, which is related to the increased synthesis of oxidants, such as hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO), and decreased antioxidant bioavailability [ 82 , 83 ]. During hypertension, plasma myeloperoxidase levels and oxidative stress are significantly increased.…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…It has been proven that ROS play an important role in the pathophysiological process of hypertension. Increased oxidative stress is an important mediator of endothelial damage in hypertension, which is related to the increased synthesis of oxidants, such as hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO), and decreased antioxidant bioavailability [ 82 , 83 ]. During hypertension, plasma myeloperoxidase levels and oxidative stress are significantly increased.…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…It was suggested that the increase in ET-1 likely occurs as a result of MALAT1 blocking the repressive activity of miR-150-5p which targets IL-1β. This study links miR-150-5p to SMC contraction, IL-1β, and hypertension [71].…”
Section: Regulation Of Il-1β By Ncrnasmentioning
confidence: 68%
“…Accumulating evidence suggested that dysregulated lncRNAs exert crucial regulatory functions in multiple processes through acting as ceRNAs to sponge microRNAs (miRNAs) [31]. MALAT1 was identified to sponge multiple miRNAs, such as miR-124-3p [32], miR-150-5p [33], miR-503 [34], miR-384 [35], and miR-22 [36]. To investigate the regulatory mechanism of MALAT1 in mGCs, we selected miRNA interactions with MALAT1 using starBase2.0 software.…”
Section: Discussionmentioning
confidence: 99%